Formulasi Dan Evaluasi Mikroemulsi Gel Minyak Chamomile Serta Uji Aktivitas Antioksidan - Sri Sulistiana; Sasanti Tarini Darijanto (Indonesian Journal of Pharmaceutical Education, 2022)
Chamomile essential oil contains various kinds of chemical compounds that was useful for skin. One of them was capable to provided good protection against free radicals. The aim of this study was to develop topical antioxidant formulation in the form of microemulsion gel that had good stability and safe for skin. This study began with determined oil concentration to incorporated into microemulsion formula.Furthermore, optimization of the surfactant, cosurfactant and carrier oil concentration to produced clear microemulsion. The evaluation of microemulsion include of organoleptic, pH, viscosity, oil droplet size, oil droplet morphology, freeze thaw test and antioxidant activity test for 28 days. Then microemulsion was incorporated into gel base to form microemulsion gel. The evaluation of microemulsion gel include of organoleptic, pH, viscosity, freeze thaw test, antioxidant activity test and irritation test. Optimization results of surfactant, cosurfactant and carrier oil which can produced clear microemulsion were Tween 80 30%, PEG 400 10% and Virgin Coconut Oil (VCO) 5%. Microemulsion had good stability indicated by pH range of 5 during stored at room temperature and climatic chamber with 75% Relative Humidity, viscosity range from 11 to 12 cps, stable droplets size below 50 nm, and no phase separation observed in centrifugation and freeze thaw test. Chamomile oil microemulsion IC50value of 84.223 ppm. Chamomile oil microemulsion gel was also had good stability indicated by pH value was remain in neutral pH range (7), viscosity from 903 to 967 cps, and no phase separation in freeze thaw test. microemulsion gel IC50 value of 80,785 ppm. Chamomile oil microemulsion gel was not irritated the skin with primary irritation index 0. The results in this study showed that Chamomile oil microemulsion gel had good stability, had antioxidant activity and does not irritated.